Identitas Budaya dalam Novel Kembar Keempat Karya Sekar Ayu Asmara: Kajian Postmodernisme - Dewi Nur Fitriana (Academica: Journal of Multidisciplinary Studies, 2017)
This article tries to examine cultural identity in novel Kembar Keempat written by Sekar Ayu Asmara by exposing postmodernism characteristic. This research uses descriptive-analysis method that is used to review postmodernism from Jean-Francois Lyotard. The result shows that in novel Kembar Keempat from Sekar Ayu Asmara, there is culture identity from postmodernism view of religion: as liberation and reformation, evasion of identity and masking: as shaping impression, and culture adaption: as a culture expression that borderless.Keywords:Postmodernism, Culture identity, Kembar keempat